2005
DOI: 10.1021/jp0475234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ion Size Effects in the Diffuse Double Layer with Use of an Integral Equation Approach

Abstract: An analytical expression is developed for the potential drop across the diffuse layer phi(d) in terms of a cubic polynomial in the corresponding estimate in the Gouy-Chapman approximation, phi(d)(GC). The coefficients of this polynomial are defined in terms of the MSA volume fraction eta and the reciprocal distance parameter Gamma. The resulting expression is shown to describe the Monte Carlo estimates of phi(d) obtained in a primitive level simulation of diffuse layer properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The analysis of the values of the diffuse layer potential calculated according to the Monte Carlo method as well as generalized mean spherical approximation [41][42][43] would give more information.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the values of the diffuse layer potential calculated according to the Monte Carlo method as well as generalized mean spherical approximation [41][42][43] would give more information.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the Monte Carlo simulations are discussed in our previous work [25]. The MC calculations were performed for three different ionic sizes, five different concentrations, and eight different positive charge densities.…”
Section: Comparisons With Monte Carlo Simulationsmentioning
confidence: 99%
“…Henderson and Blum [20,21] showed that these same integral equations could be solved in a non-iterative manner if the ion-wall correlation functions were assumed to be those given by GC theory. This method, hereinafter referred to as the HB approach, has been extended in several recent papers [22][23][24][25][26]. However, Henderson and Blum [20] clearly state that the limitation of their method is that it computes only the potential drop across the diffuse layer, but not the ion-wall correlation functions or potential profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Later work by Fawcett and Smagala showed that the HB estimates of Ξ 0 and H 0 are not sufficiently good especially for higher values of the field E . They obtained improved expressions for Ξ 0 and H 0 by forcing the value of φ d to agree with MC estimates of this quantity.…”
Section: Integral Equation Approach and The Msa Parametersmentioning
confidence: 98%